Bandgap and Wave Propagation Properties of 2D Curved and Chiral Hybrid Star‐Shaped Metamaterials. Issue 2 (16th November 2022) - Xin, Yajun; Zhang, Kun; Du, Xiuhong; Ding, Qian; Yan, Qun; Sun, Yongtao; Cheng, Shuliang; Wang, Liang
Abstract : Designing artificial microstructural metamaterials that fulfill the single‐phase vibration dampening and lightweight twin goals is challenging and critical. 2D curved and chiral hybrid star‐shaped metamaterials (CCHSM) are proposed to perform vibration reduction filtering in the midfrequency region by combining the properties of chiral structure and concave structure. The generating process of the bandgap of in‐plane elastic waves, the properties of directional attenuation, and the flow direction of energy in the dispersion curve are examined using the modal shape, dispersion surface, and group velocity. In a specific frequency range, the equivalent medium parameters satisfy the conditions of negative refraction transverse and longitudinal waves, so the structure also has double‐negative characteristics. The filtering performance is validated using the CCHSM periodic plate structure and a finite‐element simulation of transmission loss. In addition, the correlation between wave attenuation characteristics and structural parameters is explored. The radius of the circular arc and the deflection angle of the connecting rod have a significant impact on the frequency range of the structural bandgap. The results show that the created simple‐configured, single‐phase lightweight acoustic metamaterials exhibit strong local resonance properties and double‐negative features. Abstract : This work is focused on the wave propagation characteristics of a 2D curved and chiral hybrid star‐shaped metamaterial in the range of 0–6000 Hz, and the research demonstrates that the structure has greater vibration reduction and filtering effect. The creation mechanism of the structural bandgap is investigated, as well as the anisotropy of its energy flow direction. In addition, the structure's double‐negative characteristics in a certain frequency band are discovered.